Trichotillomania: A Case Study of Chronic Hair Pulling Disorder - Crystal Johannes (International Journal of Indian Psychȯlogy, 2024)
This case study looks forward to the compulsive behaviour of a 14-year-old female who has been brought to a mental health professional because of her severe hair pulling behaviour. The patient is a student who has been showing symptoms of trichotillomania for the last 6 months. Her mother decided to bring her to a mental health professional after witnessing her symptoms get worse since the last two days compared to the last 6 months of her first showing signs of hair pulling. The patient admits to be in stress because of personal issues like arguments and disagreements between herself and her best-friend which led to her feel the compulsion of pulling out her hair and depict this behaviour. Excessive hair pulling has resulted in feelings of shame and becoming socially avoidant due to the way she looks. She has also gone down on her academics because of the different ways her disorder has affected her life. Her treatment includes a mixture of therapies like Cognitive Behavioural Therapy (CBT), Habit Reversal Therapy, group therapy, peer support and medications like anti-depressants to help reduce the impulse of pulling her hair and make her aware of the habit and slowly teach how to break that habit.